THEOLOGICAL AND PHILOSOPHICAL PERSPECTIVES ON EMOTIONAL DESIGN IN AI AND VIRTUAL REALITY LEARNING: EXPLORING SPIRITUAL FORMATION AND RELIGIOUS EDUCATION - Yu, Hanlu (European journal for philosophy of religion, 2025)
The increasing integration of artificial intelligence and virtual reality in online learning platforms has raised profound philosophical and theological questions regarding human cognition, emotional engagement, and spiritual formation. However, current virtual learning environments often overlook the significant role of emotional and affective factors in shaping user experience, particularly in the context of religious education and moral development. This study explores an emotionally designed virtual interactive learning platform, incorporating a philosophical inquiry into how technology-mediated learning affects human emotions, ethical reasoning, and spiritual growth. Utilizing a MacBERT-BiSRU-AT emotion classification model, this research examines user emotional responses to virtual learning interactions, achieving an F1 score of 91.34% with efficient processing time. Findings reveal that emotionally responsive design enhances learners’ engagement, mitigates negative emotional experiences, and improves satisfaction, with over 85% of users expressing positive responses. The implications of this study extend beyond technological advancements, addressing deeper philosophical concerns about the nature of learning, digital embodiment, and the intersection of artificial intelligence with religious pedagogy. By considering users’ emotional and spiritual needs, the study suggests that emotionally intelligent design can enrich online religious education, fostering a more profound engagement with theological discourse, moral reflection, and community-based learning. Future research should further explore how AI-driven emotional design influences religious cognition, ethical development, and the metaphysical dimensions of virtual learning environments.